1977
DOI: 10.1111/j.1600-0404.1977.tb05660.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Activity in Cerebrospinal Fluid

Abstract: Lysozyme activity was measured in cerebrospinal fluid (CSF) from 114 patients with inflammatory (bacterial and serous meningitis, polyradiculitis, encephalitis) and non-inflammatory (multiple sclerosis, CNS tumors, cerebral vascular diseases) CNS diseases. Highly elevated values were found consistently in patients with bacterial meningitis. Elevated values were found also in patients with encephalitis, polyradiculitis, multiple sclerosis and CNS tumors, but a considerable overlapping between these groups and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“… 20 Correlations between soluble MAC components and BBB dysfunction is known from patients with traumatic brain injury, 45 and the positive correlation between complement C9 and age has previously been observed in AD 46 . Earlier studies have reported increased levels of CSF lysozyme as part of an inflammatory reaction to a variety of CNS pathologies 47 . Passage of lysozyme from blood through an impaired BBB as well as local production by microglia within the CNS, have been suggested as the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“… 20 Correlations between soluble MAC components and BBB dysfunction is known from patients with traumatic brain injury, 45 and the positive correlation between complement C9 and age has previously been observed in AD 46 . Earlier studies have reported increased levels of CSF lysozyme as part of an inflammatory reaction to a variety of CNS pathologies 47 . Passage of lysozyme from blood through an impaired BBB as well as local production by microglia within the CNS, have been suggested as the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…As stressed by others (Delpech & Lichtblau 1972, Ganrot & Laurel1 1974, Tourtelotte 1970) the ratios S-AlbumidSp-Albumin and Sp-IgG X S-AlbumidS-IgG x Sp-Albumin have the advantage over the determination of total protein, albumin or IgG in cerebrospinal fluid that variance of the serum concentrations of IgG and albumin is corrected for; hence, lquantitative information is obtained on the size of the barrier for the passage of albumin from blood to cerebrospinal fluid and on the synthesis of IgG in the central nervous system. Though informative, the use of these ratios in diagnostic delineation is hampered by the fact that values outside the reference intervals occur in a variety of neurological diseases (Hansen et al 1977, Olsson & Petterson 1976.…”
Section: Discussionmentioning
confidence: 99%
“…Though informative, the use of these ratios in diagnostic delineation is hampered by the fact that values outside the reference intervals occur in a variety of neurological diseases (Hansen et al 1977, Olsson & Petterson 1976.…”
Section: Patient Data On S-alburnin/sp-albumin and Sp-lgc )< S-4ibummentioning
confidence: 99%
“…-der Qualität und Richtigkeit in Abhängigkeit von den zugrunde liegenden Substraten und Meßver-fahren -sowie in den Angaben der katalytischen Aktivität in Einheiten oder Gewicht pro Völumeneinheit zu unterschiedlichen Ergebnissen geführt (13,7,9 …”
Section: Methodenunclassified